Poster 218: Biomechanical Function of the Lateral Meniscus Posterior Root and Meniscofemoral Ligaments: A Computational Study. Issue 7 (30th July 2022) - Ahsan, Zahab; Razu, Swithin; Zhu, Andrew; Jahandar, Hamid; Imhauser, Carl; Wickiewicz, Thomas; Nawabi, Danyal; Pearle, Andrew; Patel, Ronak
Objectives: Tear of the posterior root of the lateral meniscus (LMPR[ICP1] ) is commonly associated with ACL rupture. Surgical repair of the LMPR is indicated to stabilize the knee and protect the knee from progressive osteoarthritis. However, this surgery may be technically challenging or the location of the tear may not support anatomic repair to the tibial footprint. Even in the setting of a torn LMPR, a common intraoperative observation is that the anterior (Humphrey) meniscofemoral ligament (aMFL) remains intact. We denote this constellation as the HIRO lesion (Humphrey Intact, Root Out). This studied utilized a computational model of the knee to understand load sharing between the ACL, LMPR, and the MFLs in response to pivoting maneuvers. We hypothesized that (1) lateral compartment ATT would be greater in the knee with a combined deficiency of the LMPR and MFLs compared to intact MFLs (i.e. HIRO lesion, Figure 1) and that (2) the ACL force would be lower in the presence of a HIRO lesion as compared to combined LMPR and MFL injury. Methods: A previously developed computational model of the native tibiofemoral joint was utilized. The model including geometries of the tibia, femur, cartilage and menisci incorporating average properties for ligaments, capsule, meniscal attachments, and MFLs. Multiplanar torques simulating a pivoting maneuver were applied to the computational model at 30° of flexion, consisting of valgus (8 Nm), and internal rotation (4 Nm) to assess the impact of simulated sectioning of the ACL, LMPR, and MFLs. Lateral compartment anterior tibial translation and force carried by the ACL, LMPR, and each MFL were assessed at the peak applied pivoting loads. Results: With all structures intact, peak applied pivoting loads resulted in lateral compartment anterior tibial translation of 10.4 mm. With sequential ligament sectioning, lateral compartment anterior translation increased by 0.5 mm with LMPR deficiency; 5.8 mm with ACL deficiency; 8.5 mm with combined LMPR and ACL deficiency; and 8.9 mm with combined LMPR, ACL, and aMFL deficiency. Force carried by the ACL was 100 N at baseline; this increased by 12 N with LMPR deficiency and by an additional 1 N with combined sectioning of the LMPR and both MFLs. The intact LMPR saw an increase in force by 18 N with ACL deficiency from baseline. The aMFL force increased by 12 N with LMPR sectioning and by an additional 4 N with combined LMPR and ACL deficiency. The posterior MFL did not see force with simulated pivot shift testing at 30° knee flexion. Conclusions: A HIRO lesion results in a 14% increase in lateral compartment ATT (versus ACL deficiency alone) compared to a 16% increase when both the LMPR and MFLs are sectioned. While the ACL saw 12% increased force with a HIRO lesion, there was a 1 N increase in ACL force with combined LMPR and MFL sectioning. The load-bearing role of the aMFL was more pronounced with combined ACL and LMPR tear compared to LMPR tear with intact ACL. The biomechanical model confirms that, during a pivot shift, the LMPR has a primary role in lateral compartment ATT and load-sharing with the ACL compared to the aMFL. Surgeons should attempt to repair the LMPR with ACL reconstruction. Figure 1. Arthroscopic image demonstrating Humphrey Intact Root Out (HIRO) lesion in a 34-year-old male patient with combined anterior cruciate ligament/ lateral meniscus posterior root (LMPR) injury. The lateral meniscus (LM) body is disrupted from the LMPR footprint as a consequence of a radial tear (note the gap in the tissue continuity from LM body to LMPR). The anterior meniscofemoral ligament of Humphrey is visible with robust attachment to LM body connecting to the medial femoral condyle. LFC = Lateral femoral condyle (visualized in figure 1B). Table 1. Lateral compartment ATT and forces subjected to ACL, LMPR, aMFL and pMFL as outputs of a computational cadaveric knee model subjected to peak applied pivoting loads at 30° of flexion, consisting of valgus (8 Nm) and internal rotation (4 Nm).